Managing the transition to central bank digital currency - Katrin Assenmacher; Massimo Minesso Ferrari; Arnaud Mehl; Maria Sole Pagliari (European Central Bank (ECB), 2024)
We develop a two-country DSGE model with financial frictions to study the transition from a steady-state without CBDC to one in which the home country issues a CBDC. The CBDC provides households with a liquid, convenient and storage-cost-free means of payments which reduces the market power of banks on deposits. In the steady-state CBDC unambiguously improves welfare without disintermediating the banking sector. But macroeconomic volatility in the transition period to the new steady-state increases for plausible values of the latter. Demand for CBDC and money overshoot, thereby crowding out bank deposits and leading to initial declines in investment, consumption and output. We use non-linear solution methods with occasionally binding constraints to explore how alternative policies reduce volatility in the transition, contrasting the effects of restrictions on non-residents, binding caps, tiered remuneration and central bank asset purchases. Binding caps reduce disintermediation and output losses in the transition most effectively, with an optimal level of around 40% of steady-state CBDC demand.
Keywords: E50; E58; F30; F41; 330; Central bank digital currency; open-economy DSGE models; steady-state transition; occasionally binding constraints